Zakat Hasil Pertanian di Desa Poncowarno Kecamatan Poncowarno Kabupaten Kebumen - Ulinni’mah, Ro’fah (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2023)
Agricultural zakat is a zakat that is imposed on a filling staple food, on a country that has sufficient nisab and haul. The crops that are obligated to pay zakat are grains and types of staple foods that are filling and durable if stored, such as rice, dates, corn, wheat and so on. The purpose of this study was to determine: (1) the implementation of zakat on agricultural products in Poncowarno village, (2) a review of Islamic law on the implementation of zakat on agricultural products in Poncowarno village. The method used is a qualitative method with interviews, observations, and documentation. The data analysis technique in this research is descriptive qualitative. The results of this study indicate that: (1) that the practice of implementing zakat on agricultural products in Poncowarno village is carried out by the community releasing the harvest they get every year for 2 seasons in the form of dried rice which will then be weighed and the zakat calculated after it is taken from net income. Then the distribution is carried out independently to the poor. (2) A review of Islamic law on the process of implementing zakat on agricultural products in the village of Poncowarno Kebumen in practice from 12 farmers 6 of them are in accordance with Islamic law because in terms of nishab they have fulfilled/achieved and issued various zakat, some are 5% and some are 10% according to the law he follows and according to the level of agricultural zakat that must be issued. The other 2 have reached the nishab but in issuing zakat it has not been according to the levels in Islamic law. While the other 4 have not reached the nishab.